Pengembangan Kurikulum Bahasa Arab Tematik Berbasis Hukum Ekonomi Syariah - Rozaanah Rozaanah; Indra Indra (SALSABIL : Jurnal Syariah dan Hukum Ekonomi, 2025)
This research aims to develop a thematic Arabic language curriculum based on Islamic economic law for students of the Faculty of Islamic Economics and Business. Employing a qualitative approach with a research and development method, this study adapts the Taba-Tyler Curriculum Design model. Through comprehensive literature review, needs analysis, and expert validation, the study produces a curriculum framework that integrates Arabic language learning with Islamic economics content. The proposed curriculum structure encompasses four proficiency levels, focusing on progressive development of language skills and understanding of Islamic economic concepts. The findings highlight the importance of thematic approaches, task-based learning, and technology integration in teaching. Key challenges identified include the need for specialized material development and teacher training. This research contributes significantly to the development of Islamic higher education, particularly in preparing graduates for the global Islamic finance industry. Recommendations for implementation and further research are presented to support sustainable curriculum development.